Psychophysiology of gymnasts: specifics of sports specialization - Chayun, D. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to investigate the psychological and physiological traits of the young athletes from the Tyumen region who participate in cheerleading, gymnastics, and aerobics, aged between 12 and 14, and 15 and 17.